The relationship between maternal education level and occupation and the nutritional status of junior high school students - Shabrina, Andini Zhafira; Nurhayati, Faridha (Citius : Jurnal Pendidikan Jasmani, Olahraga, dan Kesehatan, 2025)
Nutritional status among adolescents is shaped by a complex interplay of biological, social, and environmental factors, making it a crucial public health issue. This study aims to examine the relationship between maternal education and maternal occupation with the nutritional status of students at SMP Negeri 35 Surabaya. Using a quantitative ex post facto correlational design, the research involved 257 eighth-grade students selected through Cluster Random Sampling. Data on maternal education and occupation were collected using categorical questionnaires, while students’ nutritional status was measured through anthropometric assessments and classified using BMI-for-age indicators. The Gamma correlation test was employed to analyze the relationship between variables. The results show considerable variation in students’ nutritional status, with categories ranging from undernutrition to obesity; however, the statistical analysis indicates no significant correlation between maternal education (p = 0.181) or maternal occupation (p = 0.806) and students’ nutritional outcomes. These findings differ from several earlier studies suggesting that maternal characteristics influence children’s dietary habits, nutrient intake, and overall health behaviors. The absence of significant relationships in this study suggests that adolescents’ nutritional status may be influenced more strongly by broader lifestyle, environmental, or school-related factors rather than maternal background alone. Overall, the results highlight the need for more comprehensive, multi-sectoral nutrition interventions that involve families, schools, and communities to better support adolescents’ growth and development.